Pengaruh Digital Marketing, Penggunaan Promosi Endorsment, Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Merk Pakaian Sutr Heritage - Muhammad Nur Fadlil; Dwi Dewianawati; Ratna Agustina (Formosa Journal of Social Sciences (FJSS), 2022)
Digital marketing is a medium that is used as a platform to build a brand image of a product and also supports the sales function of target consumers. To increase sales, it is necessary to apply one strategy, namely ENDORSMENT. There is a relationship between digital marketing, endorsement promotion and product quality purchasing decisions on SUTR Heritage brand clothing. This research was conducted at SUTR Heritage UMKM which aims to determine whether there is an influence of digital marketing, endorsement promotion and product quality on purchasing decisions. The type of research used is quantitative research, the number of samples used by consumers or followers on Instagram with a total of 50 respondents. The technique used is the Multiple Linear Regression Analysis method, after passing the classical assumption test using the SPSS program. From the results of the study obtained multiple linear regression equation Y=8.686 + (-0.027) X1 + 0.356 X2 + 0.250 X3 + 3.012. The results of the t-test are significant values ​​of digital marketing variables 0.875, endorsement promotions 0.012, and product quality 0.097 which means that digital marketing and product quality have no effect, while endorsement promotion variables affect purchasing decisions. The results of the f test get a value of 0.000 (0.000 <0.05) which means that the languages ​​of the 3 variables (X) have a simultaneous effect on the variable (Y). The value of the coefficient of determination is 0.324, which means that it simultaneously has a positive and significant effect on the purchasing decision variables. There is a simultaneous influence between the digital marketing variables, endorsement promotions, and product quality on the purchasing decision variables of 32.4%.